2020
DOI: 10.1007/s10549-020-05524-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, 3-arm, neoadjuvant, phase 2 study comparing docetaxel + carboplatin + trastuzumab + pertuzumab (TCbHP), TCbHP followed by trastuzumab emtansine and pertuzumab (T-DM1+P), and T-DM1+P in HER2-positive primary breast cancer

Abstract: Purpose The standard of care in the neoadjuvant setting for human epidermal growth factor receptor 2 (HER2)-positive breast cancer is dual HER2-targeted therapy. However, a need to minimize treatment-related toxicity and improve pathological complete response (pCR) rates, particularly in luminal HER2-positive disease, exists. Methods Neopeaks, a randomized, phase 2 study, compared docetaxel + carboplatin + trastuzumab + pertuzumab (TCbHP; 6 cycles; group A), TCbHP (4 cycles) followed by trastuzumab emtansine +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Finally, our study included 36 clinical trials published between 2007 and 2020, involving 89 treatment arms, focusing on neoadjuvant therapy for HER2-positive breast cancer, and involving a total of 10,379 patients ( Supplemental File 2 ). 6 , 8 , 9 , 11 , 22 56 Some of the studies compared chemotherapy with targeted therapy, and others compared dual-target therapy with single-target therapy. Five trials evaluated the efficacy of T-DM1 in neoadjuvant therapy, and another five focused on trastuzumab biosimilars.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our study included 36 clinical trials published between 2007 and 2020, involving 89 treatment arms, focusing on neoadjuvant therapy for HER2-positive breast cancer, and involving a total of 10,379 patients ( Supplemental File 2 ). 6 , 8 , 9 , 11 , 22 56 Some of the studies compared chemotherapy with targeted therapy, and others compared dual-target therapy with single-target therapy. Five trials evaluated the efficacy of T-DM1 in neoadjuvant therapy, and another five focused on trastuzumab biosimilars.…”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated in our study, T-DM1-containing regimens also show great efficacy, especially when combined with other targeted drugs or chemotherapies. 51 , 54 Compared with the traditional targeted therapy, the use of antibody drug conjugate (ADC) to increase the drug concentration in tumour cells may further enhance efficacy. However, we also noticed that ‘KAITLIN’, a phase III study directly comparing T-DM1 plus pertuzumab with taxane plus trastuzumab and pertuzumab after anthracycline as adjuvant therapy, did not meet its co-primary end point that T-DM1 is better than the control.…”
Section: Discussionmentioning
confidence: 99%
“…In the JBCRG-20 trial, patients were randomly assigned to three treatment regimens: (I) docetaxel, carboplatin, and trastuzumab plus pertuzumab for six cycles; (II) docetaxel, carboplatin, and trastuzumab plus pertuzumab for four cycles followed by T-DM1 plus pertuzumab for four cycles; (III) T-DM1 plus pertuzumab for four cycles, followed by two cycles of same regimen for responders or four cycles of anthracycline-based regimen for non-responders (19). The pCR rates were 57%, 71%, and 57% for group A, group B, and group C, respectively.…”
Section: Increasing the Proportion Of Patients Who Achieve Pcr With Dual Her2 Blockadementioning
confidence: 99%
“…36 Ado-trastuzumab emtansine based neoadjuvant therapy may provide better quality of life for patients and minimize toxicity when compared to chemotherapy-based treatment, but thus far it has not shown to be the best agent for neoadjuvant phase. 37 It is hypothesized that inferiority of neoadjuvant ado-trastuzumab emtansine to chemotherapy-based treatment is likely due to lack of payload bystander effects in the setting of HER2 receptor heterogeneity, toxicity limited C max and slow rate of internalization. 5,7 HER2 receptor heterogeneity is also responsible for development of resistance to the ado-trastuzumab emtansine.…”
Section: Clinical Use Controversiesmentioning
confidence: 99%
“…36 The trial concluded while ado-trastuzumab emtansine based neoadjuvant therapy has fewer side-effects, it was inferior to neoadjuvant chemotherapy-based therapy. 37 Shortcomings of ado-trastuzumab emtansine that may explain ado-trastuzumab emtansine inferiority in the KRISTINE trial include toxicity limited C max , slow rate of internalization, and lack of payload bystander effects which decreases drug effectiveness with heterogenous HER2 receptor expression and a number of resistance mechanisms. 7 These shortcomings make for great research targets to enhance function of the drug.…”
Section: Perspective On Use (Summary Paragraph On How This Drug Fits mentioning
confidence: 99%